Rasionalisasi Motif Ekonomi dan Peran Ganda Perempuan dalam Membantu Perekonomian Rumah Tangga di Desa Lodtunduh - Sriyani, Ni Nyoman; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to determine the rationalization of economic motives and the dual role of women in helping the household economy in Lodtunduh Village. This research uses a qualitative approach with a type of case study research. In the data collection process, researchers used purposive sampling with the subjects of the study being women who worked as builders or laborers transporting building materials and piled stone. The number of informants used in this study was 1 key informant and 10 main informants. The data collection methods used are observation, interviews, and documentation. The data analysis technique used in this study is qualitative analysis from Miles and Huberman, starting from data collection, data reduction, data presentation, and conclusions. Data validity testing using source triangulation. Research results show that there are three economic motives for women to choose to become craftsmen or laborers transporting building materials and piled stone, namely meeting economic needs, meeting psychological needs, and meeting social needs. Multiple roles played by women in Lodtunduh Village have a positive impact on the economy, namely being able to help increase the husband’s income to meet household needs, as well as women who are craftsmen or laborers transporting building materials and piled stone are able to manage their time between work in the household and work as a laborer.